2018
DOI: 10.1177/0308275x18775818
|View full text |Cite
|
Sign up to set email alerts
|

It’s all you! Australian ayahuasca drinking, spiritual development, and immunitary individualism

Abstract: Ayahuasca, a psychoactive plant decoction, has spread from indigenous communities in South America to urban areas in the Americas, Europe, and Australia where it is used in neoshamanic rituals. This paper draws on ethnography of Australian ayahuasca ceremonies to examine the ways that individualism shapes the structure of ayahuasca rituals, the interpretation of visionary experiences, and notions of spiritual development. I show how the metaphors that Australian drinkers involved in this study use to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Even though the present results suggest positive prosocial effects of collective psychedelic use, qualitative studies have found a tendency, in neoshamanic settings of ayahuasca use (Gearin, 2015b;Gearin, 2016a;Rodd, 2018), for individualistic and narcissistic cultural priors to be reproduced in ideas of self-actualization and -development, which are similarly defining for New Age culture (Graf, 1986;Farias and Lalljee, 2008;Lahood, 2010;Masters, 2010) as they are for neoliberalist-entrepreneurial constructions of selfhood (Adams et al, 2019). In order for psychedelics to produce the healthy paradigm shift in psychiatry that some have predicted (Nichols et al, 2017;Schenberg, 2018), it may thus be necessary to question some of the fundamental cultural assumptions from, and into which psychedelic therapies are emerging-so that psychedelic treatments may not merely remain a "chemical holiday [.…”
Section: Implications: Toward a Biopsychosocio-cultural Approach To Pcontrasting
confidence: 92%
“…Even though the present results suggest positive prosocial effects of collective psychedelic use, qualitative studies have found a tendency, in neoshamanic settings of ayahuasca use (Gearin, 2015b;Gearin, 2016a;Rodd, 2018), for individualistic and narcissistic cultural priors to be reproduced in ideas of self-actualization and -development, which are similarly defining for New Age culture (Graf, 1986;Farias and Lalljee, 2008;Lahood, 2010;Masters, 2010) as they are for neoliberalist-entrepreneurial constructions of selfhood (Adams et al, 2019). In order for psychedelics to produce the healthy paradigm shift in psychiatry that some have predicted (Nichols et al, 2017;Schenberg, 2018), it may thus be necessary to question some of the fundamental cultural assumptions from, and into which psychedelic therapies are emerging-so that psychedelic treatments may not merely remain a "chemical holiday [.…”
Section: Implications: Toward a Biopsychosocio-cultural Approach To Pcontrasting
confidence: 92%
“…Yet one must be wary of investing too much in a vague critique of the liberal/Christian/modern individualist subject. As Rodd () notes in a study of how white, Australian neo‐shamanic ayahuasca‐drinkers process their experiences, the ‘expansive, non‐relational self’ (‘it's all you’) becomes a metaphor for transcendence that, ironically, reproduces the very modern narcissism and disenchantment that it seeks to overcome (2018: 325). To avoid methodological solipsism, it seems essential to pay attention to how persons are actually made.…”
Section: The Rise Of Networked Personhoodmentioning
confidence: 99%
“…Concerns with the over-emphasis of inner-spirituality are described extensively in new-age research ( Heelas, 2009 ; Simchai, 2009 ). In short, while new-age culture sees itself as a counter-culture, it can actually reinforce dominant cultural trends of individualism, something which has been observed in some neoshamanic ayahuasca circles as well ( Gearin, 2015 ; Rodd, 2018 ; Apud, 2020a ). For example, some Australian ayahuasca practitioners believe that “The primacy of the individual is reflected in the idea that social transformation is only possible after the individual transforms their consciousness” ( Rodd, 2018 ).…”
Section: Introductionmentioning
confidence: 96%
“…The facilitators blend indigenous practices with some forms of Western therapeutic practices, new-age , religious elements, and other spiritual traditions and practices based on their own identity, or local to their countries. In many cases, people tend to return to the same group, and communities are formed around these ayahuasca ceremonies ( Hanegraaff, 2011 ; Rodd, 2018 ). While these groups often evolve into communities, the language they use and intentions for taking ayahuasca are still centered on therapeutic ends and personal processes ( Gearin, 2015 ; Rodd, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation